Qualitative Study of Cultural Tourism Policy in Iran: A Comparison of Rafsanjani, Khatami and Ahmadinejad Governments - Hemmatiha, Saeed; Momeni, Mehdi; Saberi, Hamid (Revista Publicando, 2018)
The present study seeks to study the policy of cultural tourism in Iran after the Islamic Revolution, with emphasis on Isfahan province. To achieve this goal, the cultural policies of Hashemi Rafsanjani, Khatami and Ahmadinejad governments have been investigated in a comparative way. The research method is qualitative and is based on qualitative content analysis. Data collection tools are semi-structured interviews. To this end, semi-structured interviews have been conducted with 21 experts in the field of cultural tourism in Isfahan province. Also, the statistics in the statistical journals as well as the laws and regulations legislated on cultural tourism have been used in each of the above-mentioned governments. Findings of the research indicate that Ahmadinejad's government has been somewhat more successful in the parameter of efficient management. In terms of political interaction, Khatami's government has shown a better performance. In general, Ahmadinejad's government has been more successful than Hashemi Rafsanjani's and Khatami's governments in allocating credits to cultural tourism. In the field of cultural policy, Khatami's government generally worked better than the other two governments, Ahmadinejad's government ranks the second and Hashemi's is the last. Ultimately, in the field of macro strategies, Khatami's government worked relatively better than the other two governments, Ahmadinejad government is the second and, ultimately, the government of Hashemi Rafsanjani ranks the lowest.